TAHLIL AS-SIRA' AN-NAFSIY LISY-SYAKHSHIYYAH AR-RA’ISIYYAH FI QISHSHAH AL-UFUQ WARA'A AL-BAWABAH LI GHASSAN KANAFANI: DIRASAH ADABIYAH NAFSIYYAH - Siti Khofifah; Hatta Raharja; Farhan Firdaus; Zughrofiyatun Najah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2026)
The id, ego, and superego are understood as distinct psychic elements that interact dynamically in shaping human personality. The fundamental theory of this personality structure was proposed by the renowned psychoanalyst, Sigmund Freud. This article examines the application of these concepts to the character Ali in Ghassan Kanafani's short story Al-Ufuqu Wara’a Al-Bawabah. This work is part of the anthology Ardhul Burtuqal Al-Hazin, which chronicles the suffering of the Palestinian people following the 1948 Nakba, with a focus on the psychological trauma of youth in exile. The main focus of this study is to analyze how the id, ego, and superego influence Ali's behavior as he is trapped between profound grief over the death of his sister Dalal and the demands of survival amid extreme social realities. This study employs a qualitative method with a literary psychology approach based on Freud's psychoanalytic framework. The findings conclude that Ali exhibits a dominant id, particularly in his impulsive pursuit of instant relief and avoidance of emotional wounds. Meanwhile, Ali's ego functions as a mediator, forming self-defense mechanisms through a decade-long lie to preserve his inner stability. However, this ego appears paralyzed when he fails to confront physical reality upon meeting his mother. On the other hand, Ali's superego exerts intense moral pressure, manifested in deep regret and self-labeling as a "coward" due to the burden of his prolonged deception.